1996
DOI: 10.1111/j.1528-1157.1996.tb00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐Effect and Concentration‐Toxicity Relations with Lamotrigine: A Prospective Study

Abstract: This prospective study was designed to ascertain whether measurement of lamotrigine (LTG) concentrations in the epilepsy clinic could be used to predict the onset of complete seizure control or the emergence of adverse effects. LTG was initiated in doses of 25 or 50 mg daily in 69 patients with newly diagnosed or poorly controlled epilepsy and was increased monthly in 50-mg increments until the patient became seizure-free for at least 6 months or developed adverse effects that abated after a reduction in dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 14 publications
1
53
0
2
Order By: Relevance
“…Despite LTG's wide clinical use, standard npg dosage regimens continue to be used even though they may often be suboptimal because of the high variability found in CL values in the target population [7,10,[13][14][15][16][17][18] . This observation, together with previous studies that have established definable relationships between LTG blood concentrations and therapeutic and toxic effects [19][20][21] , justify TDM as an indicator of drug exposure for the individualization of LTG doses [4][5] . In this sense, the availability of a population kinetic model able to predict LTG concentrations for different situations is essential for the correct selection of the dosage schedules based on a Bayesian approach.…”
Section: Discussionmentioning
confidence: 98%
“…Despite LTG's wide clinical use, standard npg dosage regimens continue to be used even though they may often be suboptimal because of the high variability found in CL values in the target population [7,10,[13][14][15][16][17][18] . This observation, together with previous studies that have established definable relationships between LTG blood concentrations and therapeutic and toxic effects [19][20][21] , justify TDM as an indicator of drug exposure for the individualization of LTG doses [4][5] . In this sense, the availability of a population kinetic model able to predict LTG concentrations for different situations is essential for the correct selection of the dosage schedules based on a Bayesian approach.…”
Section: Discussionmentioning
confidence: 98%
“…The value of monitoring plasma concentrations of LTG has not been established, nor does the magnitude of adverse symptoms correlate with LTG plasma concen- trations (48). Because of possible pharmacokinetic interactions between LTG and other AEDs being taken concomitantly, monitoring of plasma levels of LTG and concomitant drugs may be indicated, particularly during dose adjustments (46,4930).…”
Section: How To Prescribementioning
confidence: 99%
“…Several reports have suggested that there is no relationship between the clinical response or side effects and the plasma concentration of LTG. [1][2][3] In contrast, Johannessen and Tomson 4) reported that TDM was likely to be useful for treatment with LTG in many clinical settings. Hirsch et al 5) also reported that the incidence of side effects caused by LTG increased along with elevation of its concentration.…”
mentioning
confidence: 99%